Treatment with homodimeric interleukin-12 (IL-12) p40 protects mice from IL-12-dependent shock but not from tumor necrosis factor alpha-dependent shock. - Mattner, F (1997)
The role of interleukin-12 (IL-12) was investigated in different shock models using anti-IL-12 reagents. IL-12 is composed of two disulfide-bonded subunits, p35 and p40. The IL-12 p40 homodimer (p40)2 has been shown to be a potent IL-12 antagonist in vitro. We investigated its in vivo inhibitory capacity in different shock models of mice. We could demonstrate that (p40)2 is able to protect mice from septic shock in primarily IL-12-dependent models such as the Shwartzman reaction and lipopolysaccharide (LPS)-induced shock, whereas (p40)2 has no effect in the tumor necrosis factor alpha-dependent LPS/D-GalN shock model. In IL-12-dependent shock models, (p40)2 inhibits IL-12-induced gamma interferon production and thereby interferes with the cascade of cytokine release, finally leading to death.